The Association between Environmental Disclosure and Financial Disclosure on the Internet by Malaysian Listed Companies - Ali Saleh Ahmed Alarussi; Mohamad Hisyam Selamat; Mustafa Mohd Hanefah (Inderscience Enterprises Ltd., 2024)
The rapid growth of internet technology has made it possible for companies to directly and instantly disclose their financial and non-financial information to fulfil user needs worldwide. The purpose of this paper is to examine whether there is any association between the extent of internet financial disclosure (IFD) and the extent of internet environmental disclosure (IED) by Malaysian listed companies. The data from 194 companies were used as a sample for this study. Linear regression analysis was conducted and results show that there is a significant positive relationship between the extent of IED and the extent of IFD. The finding also indicates that the disclosure of financial and environmental information on the internet by Malaysian listed companies has improved; however, there is still much room for improvement especially in areas of environmental disclosures.